Blepharo‐cheilo‐dontic (BCD) syndrome: Expanding the phenotype, case report and review of literature. Issue 6 (9th April 2014) - Ababneh, Farouq K.; Al‐Swaid, Abdulrahman; Elhag, Ahmed; Youssef, Talaat; Alsaif, Saif
<x xml:space="preserve">Abstract</x> The combination of lagophthalmia, euryblepharon, ectropion of lower eyelids, distichiasis, bilateral cleft lip and palate, and oligodontia comprises the blepharo‐cheilo‐dontic (BCD) syndrome. This combination has been found sporadically or with positive family history and inherited as an autosomal dominant condition with variable expression. We described a Saudi boy with the cardinal signs consistent with the BCD syndrome. In addition to the common components of BCD syndrome that involve eyelids, lip, and teeth abnormalities, this patient is the third reported BCD case with imperforate anus, the second with thyroid agenesis, and the first with lumbosacral meningomyelocele. © 2014 Wiley Periodicals, Inc.